Evaluative Study On The Mastery Of Cooperative Learning Models Among Prospective Teachers At Unisma Bekasi - Amin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
The increasing demand from the education sector for Teacher Education Institutions to produce graduates with professional teaching competence must be taken seriously. This study aims to evaluate the extent of mastery of cooperative learning models among prospective teacher students at Faculty Of Teacher Training And Education and Faculty Of Islamic Studies of Universitas Islam 45 Bekasi. A quantitative approach was employed using a survey method through questionnaires and concept mastery tests. The study population comprised 284 students, with a sample of 135 selected respondents. Findings reveal that, on average, prospective teachers mastered approximately 4.64 cooperative learning models, equivalent to 4 to 5 models. No significant differences were found in model mastery among students of Primary Teacher Education, Islamic Education, and Geography Education programs. Parental occupation had no significant effect on the mastery level. However, significant correlations were found between the level of mastery and factors such as the choice of teaching practice location, reasons for selecting the practice school, and interest in participating in learning model clinics. These findings highlight the importance of individual experiences and intrinsic motivation in mastering cooperative learning models. This study contributes to the mapping of prospective teachers’ readiness and serves as a foundation for developing clinical-based training programs within teacher education curricula.